2022
DOI: 10.1002/ptr.7647
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bergamot (KoksalGarry) supplementation on lipid profiles: A systematic review and meta‐analysis of randomized controlled trials

Abstract: This systematic review and meta‐analysis were conducted to evaluate the impact of bergamot (KoksalGarry) and its nutraceutical compounds on lipid profiles. PubMed, Web of Knowledge, Scopus, and Google Scholar searched for relevant articles. Trials investigating the effect of oral bergamot supplementation on serum levels of total cholesterol (TC), triglyceride (TG), low‐density lipoprotein cholesterol (LDL‐C), and high‐density lipoprotein cholesterol (HDL‐C) in adults were included. The mean differences and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
(163 reference statements)
0
3
0
Order By: Relevance
“…Laganà et al [ 79 ] studied the effect of replacing wheat flour in manufactured cookies with pressed and dried bergamot pulp. Bergamot is a source of polyphenolic compounds, such as neoeriocitrin, rutin, neohesperidin, and naringin [ 80 ]. A citrus by-product known as Pastazzo caused significant disposal problems in recent years [ 81 ].…”
Section: Changes In Chemical Composition and Antioxidant Activitymentioning
confidence: 99%
“…Laganà et al [ 79 ] studied the effect of replacing wheat flour in manufactured cookies with pressed and dried bergamot pulp. Bergamot is a source of polyphenolic compounds, such as neoeriocitrin, rutin, neohesperidin, and naringin [ 80 ]. A citrus by-product known as Pastazzo caused significant disposal problems in recent years [ 81 ].…”
Section: Changes In Chemical Composition and Antioxidant Activitymentioning
confidence: 99%
“…In particular, a meta-analysis of nine randomized clinical trials on the effects of artichoke extract on plasma lipids showed TC (weighted mean difference (WMD): −17.6 mg/dL, 95%CI: −22.0 to −13.3, p < 0.001), LDL-C (WMD: −14.9 mg/dL, 95%CI: −20.4 to −9.5, p = 0.011) and TG (WMD: −9.2 mg/dL, 95%CI: −16.2 to −2.1, p < 0.011), without a significant change in HDL-C concentrations [ 38 ]. Moreover, a further recent meta-analysis of 14 randomized clinical trials has concluded that bergamot extracts are able to decrease TC (WMD: −63.6 mg/dL; 95%CI: −78.0 to −49.2; p < 0.001), TG (WMD: −74.7 mg/dL; 95%CI: −83.6 to −65.9; p < 0.001), LDL-C (WMD: −55.4 mg/dL; 95%CI: −67.3 to −43.6; p < 0.001) and increase HDL-C (WMD: 5.8 mg/dL; 95%CI: 3.3 to 8.3; p < 0.001), respectively, in humans [ 39 ]. However, in both cases, the best lipid-lowering effect has been obtained with more than one tablet per day [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each 100 mL bottle contained: Kiwi [ 29 ], Annurca apple [ 22 ], bergamot [ 30 ] and grape juice [ 31 ]; Two grams of phytosterols; Red yeast rice containing 2.9 mg of monacolins from Monascus purpureus ; 100 mg of berberine complexed with β-cyclodextrin. …”
Section: Methodsmentioning
confidence: 99%